Human papillomavirus and occupational exposure: The need for vaccine provision for healthcare providers - Selim Afsar; Maksuda Hossain; Muntaha Islam; Hailey Simmonds; Ashley A. Stillwell; Kristina A. Butler (Taylor & Francis Group, 2024)
ABSTRACTTo probe the understanding of healthcare providers regarding occupational exposure to human papillomavirus and their knowledge about human papillomavirus vaccination in relation to the American Society for Colposcopy and Cervical Pathology (ASCCP) recommendations. In this cross-sectional study, the healthcare providers at Mayo Clinic Arizona, Florida, and Minnesota were delivered an electronic survey. The survey was completed by 349 healthcare providers, with one respondent excluded for inconsistent entry. The mean age of respondents was 42.7 ± 10.9, and of those, 68% were female and 32% were male. Of the unvaccinated respondents, 43.3% were ≤ 45 y of age (eligible for vaccination), while those vaccinated formed 41% of the respondents. Healthcare providers are highly concerned about their cancer safety, as shown by their awareness of occupational human papillomavirus hazards and broad knowledge about vaccine efficacy. The use of personal protective equipment varied widely, including eyewear, double gloving, procedural face mask, N95 face mask, and/or nothing. Human papillomavirus and cancer risk was clearly perceived by healthcare providers. For professions, pairwise comparisons revealed that nurse practitioners, physician assistants, certified registered nurse anesthetists, and allied healthcare providers had lower scores than medical doctors. Despite the high level of understanding among healthcare providers of occupational human papillomavirus exposure, only a few of them knew of the recommendations of the ASCPP for vaccination of healthcare providers treating human papillomavirus-related diseases. In such cases, most of those surveyed embraced vaccination, which was considered 100% safe by medical doctors and allied health professionals.